2022
DOI: 10.3390/molecules27103117
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolics and Anthocyanins Contents and Antioxidant Activity in Four Different Aerial Parts of Leafy Sweet Potato (Ipomoea batatas L.)

Abstract: Leafy sweet potato (Ipomoea batatas L.) is an excellent source of nutritious greens and natural antioxidants, but reports on antioxidants content and activity at buds, leaves, petioles, and stems are scarce. Therefore, the total phenolics content (TPC), total anthocyanins content (TAC), and antioxidant activity (assessed by DPPH and ABTS radical scavenging activities and ferric reducing antioxidant power (FRAP)) were investigated in four aerial parts of 11 leafy sweet potato varieties. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
0
10
1
Order By: Relevance
“…The mineral and vitamin composition of purple sweet potato leaves is higher than spinach, cabbage, asparagus, broccoli, and another vegetable [24]. These purple sweet potato leaves as green vegetables are rich in phytochemicals and abundant polyphenols, but in some countries even in Jayapura itself, most of them are discarded and used as animal feed because the leaves when consumed feel hard [8,[16][17][18] The mineral and vitamin composition of purple sweet potato leaves can be seen in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mineral and vitamin composition of purple sweet potato leaves is higher than spinach, cabbage, asparagus, broccoli, and another vegetable [24]. These purple sweet potato leaves as green vegetables are rich in phytochemicals and abundant polyphenols, but in some countries even in Jayapura itself, most of them are discarded and used as animal feed because the leaves when consumed feel hard [8,[16][17][18] The mineral and vitamin composition of purple sweet potato leaves can be seen in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antisionins, flavonoids, and polyphenols in purple sweet potato leaves has provided health benefits including anti-cancer [9] anti-modulation [10], antimutagenic [11], antihypertensive [12], antidiabetic [13], heart and liver protection [14,15]. As a phytochemicalenriched green vegetable, purple sweet potato (Ipomoea batatas .L) leaves are popular in many countries, but a study [8], found the fact that purple sweet potato leaves, which are abundant in polyphenols, are underutilized, while also in some countries purple sweet potato leaves are not known for their benefits and use so that these leaves are mostly discarded and used as livestock food [12,16,17] as well as in Jayapura the tubers are utilized but the leaves are not consumed and are only used as fodder, while in the community many are malnourished. Sweet potato leaves are a cheap and [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tere was a large variation in the phenolics content among the sweet potato varieties [27], and the contents of phenolic acid derivatives are described in Table 6 and Figure 2. 3,5-dicafeoylquinic acid was the dominant phenolic acid derivative in all varieties.…”
Section: Bioactive Chemicalsmentioning
confidence: 97%
“…Nutritional analysis was conducted using standard methods [33] for dry matter (DM), ash, crude protein, and ether extract. Neutral detergent ber (NDF) and acid detergent ber (ADF) were determined using the methods outlined by Goering and Van Soest [35]. A sample of 20g of fresh silage was squeezed with 180mL distilled water using a blender at a higher speed for 30 sec [16].…”
Section: Nutritional Analysismentioning
confidence: 99%